(untitled) (Journal of Health, Population and Nutrition, 2010)
There is currently no public financial system that fully covers enteric fever suspects in China. This study aimed at documenting the level of access to definitive diagnostic procedures, especially haemoculture, for these patients and examining the effect of health insurance on access to such care. A hospital-based cross-sectional study was conducted in six counties of Yunnan province, using a structured questionnaire and data extraction from medical records. In total, 714 subjects were recruited. Chi-square test and logistic regression were employed for analysis of data. The majority of the subjects were young adults (52%) and farmers (55%) from low-income families (49%). Only 407 (57%) could afford haemoculture routinely advised by their doctors. Of these, 123 (30%) had haemoculture positive for Salmonella Typhi. After adjustment for income, not getting haemoculture was marginally associated with percentage of reimbursement from the insurance (p value for trend=0.047). Illiteracy was also an independent risk factor for this outcome. The poor coverage of haemoculture for patients suspected of having enteric fever in this endemic area was due to financial barrier. The current health-insurance system inadequately relieved the problem. Further financial reform to help patients suspected with enteric fever is required. Key words: Cross-sectional studies; Diagnosis, Laboratory; Haemoculture; Health expenditure; Health insurance; Healthcare; Typhoid; China DOI: 10.3329/jhpn.v28i1.4523 J Health Popul Nutr 2010 Feb; 28(1): 53-60